ANALISIS KOMPONEN KIMIA EKSTRAK METANOL FRAKSI PETROLEUM ETER DAUN EUPATORIUM ODORATUM DENGAN GC-MS - Purwati Purwati; Sabirin Matsjeh (Universitas Jenderal Soedirman, 2008)
The purpose of this investigation was to analize the organic compounds of Eupatorium odoratum leaf and identification of the compounds using Gas Chromatography Mass Spectrometry (GC-MS). The sample was soaked in metanol. The extract of metanol was partitioned using petroleum ether. The extracts obtained were analyzed and identified by GC-MS. The results showed that in the extract of petroleum ether contained the organic compounds: germacrene, isocaryophyllene, 2,6,6,9-tetramethyl-1,4,8-cycloundecatriene, 1-methyl-5-methylene-8-(1-methylethyl)-1,7-cyclodecadiene, 1,2,4a,5,8,8a-hexahydro-4,7-dimethyl-1-(1-methylethyl) naphthalene, 1,12- dodecanediol, octahydro-1-(2-octyldecyl) pentalene, 3,7,11,15-tetramethyl-2-hexadecen-1-ol, methyl (12-acetyloxy)-9-octadecanoic, bis (2-ethylhexyl) phthalat, farnesol, 4,22-cholestadien-3-one and 1,2,3,5,6,7,8,8a-octahydro-1,4-dimethyl-7-(1-methylethenyl) azulene. In the extract of ethyl acetate contained the organic compounds: methyl heptadecanoic, hexadecanoic acid, methyl 13-octadecenoic, 14,16-octadecadienal and octadecanoic acid.